Red Light Stimulates Feeding Motivation in Fish but Does Not Improve Growth - Volpato, Gilson L. [UNESP]; Bovi, Thais S. [UNESP]; de Freitas, Renato H. A. [UNESP]; da Silva, Danielle F. [UNESP]; Delicio, Helton C. [UNESP]; Giaquinto, Percilia C. [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Public Library of Science (PLoS), 2013)
Nile tilapia fish were individually reared under similar light levels for 8 weeks under five colored light spectra (maximum wavelength absorbance): white (full light spectrum), blue (~452 nm), green (~516 nm), yellow (~520 nm) or red (~628 nm). The effects of light on feeding, latency to begin feeding, growth and feed conversion were measured during the last 4 weeks of the study (i.e., after acclimation). We found that red light stimulates feeding, as in humans, most likely by affecting central control centers, but the extra feeding is not converted into growth. © 2013 Volpato et al.
Keywords: animal behavior; animal experiment; blue light; controlled study; feeding behavior; food intake; light exposure; motivation; nonhuman; Oreochromis niloticus; photoacclimatization; photostimulation; red light; spectral sensitivity; white light